Frost Heave Deformation Analysis Model for Microheave Filler - Chai, Jinfei (2019)
With the rapid development of high-speed railway, high-speed railways pose new requirements on subgrade frost heave deformation control. Microheave in conventional non-frost-heave filler cannot meet the requirements of high-speed railways for high levels of smoothness and stability and threaten high-speed train operation safety. To solve problems of seasonal permafrost region subgrade filler microheave in China, combined laboratory test and theoretical analysis, this research analyzed the physical properties of frost heave influencing factors for microheave filler. The influence of skeleton grain during frost heave formation is revealed. The microheave filler frost heave development mechanism is investigated. On this basis, based on the principle of minimum energy, a frost heave calculation formula for microheave filler is deduced, and a frost heave deformation analysis model for microheave filler is created. In addition, the effectiveness of the model is demonstrated in an indoor test. This study provides a theoretical reference for controlling the frost heaving deformation of railway subgrade.